Mutual and Thermal Diffusivities as Well as Fluid-Phase Equilibria of Mixtures of 1-Hexanol and Carbon Dioxide - Wu, Wenchang; Klein, Tobias; Kerscher, Manuel; Rausch, Michael Heinrich; Koller, Thomas Manfred; Giraudet, Cédric; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2020)
This work contributes to an improved understanding of the fluid-phase behavior and diffusion processes in mixtures of 1-hexanol and carbon dioxide (CO2) at temperaturesaround the upper critical end point (UCEP) of the system. Raman spectroscopy and dynamic light scattering were used to determine the composition at saturation conditions as well as Fick and thermal diffusivities. An acceleration of the Fick diffusive process up to CO2 mole fractions of about 0.2 was found, followed by a strong slowing-down approaching vapor−liquid−liquid equilibrium or critical conditions. The acceleration of the Fick diffusive process vanished at temperatures much higher than the UCEP. Experimental Fick diffusivity data were compared with predictions from equilibrium molecular dynamics simulations and excess Gibbs energy calculations using interaction parameters from the literature. Both theoretical methods were not able to predict that the thermodynamic factor is equal to zero at the spinodal composition, stressing the need for new methodologies under such conditions. Thus, new sets of temperature-dependent interaction parameters were developed for the nonrandom two-liquid model, which improve the prediction of the Fick diffusion coefficient considerably. The link between the Fick diffusion coefficient and the nonrandomness of the liquid phases is also discussed.<br